2003
DOI: 10.1007/s00213-003-1473-3
|View full text |Cite
|
Sign up to set email alerts
|

Operant responding for a visual reinforcer in rats is enhanced by noncontingent nicotine: implications for nicotine self-administration and reinforcement

Abstract: Nicotine influences operant behavior in two ways: by acting as a primary reinforcer when it is contingent upon behavior, and by directly potentiating the reinforcing properties of other stimuli through a nonassociative mechanism. Nicotine self-administration and smoking may be largely dependent upon this later action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
370
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(414 citation statements)
references
References 42 publications
40
370
1
2
Order By: Relevance
“…Recall that timeout stimuli including illumination of the house light and lever retraction were present throughout the experiment. Previous research has clearly shown that nicotine can enhance weakly reinforcing sensory stimuli (Donny et al, 2003; Chaudhri et al, 2006). More recently, this enhancement effect has been demonstrated with other nAChR agonists including varenicline (Barrett, 2014; Schassburger et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Recall that timeout stimuli including illumination of the house light and lever retraction were present throughout the experiment. Previous research has clearly shown that nicotine can enhance weakly reinforcing sensory stimuli (Donny et al, 2003; Chaudhri et al, 2006). More recently, this enhancement effect has been demonstrated with other nAChR agonists including varenicline (Barrett, 2014; Schassburger et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…First, nicotine directly strengthens operant responding (primary reinforcing effect, see Chaudhri et al, 2006). Second, nicotine enhances the incentive value of reinforcing nonpharmacological stimuli Donny et al, 2003;Palmatier et al, 2006). The dual reinforcing effects of nicotine raise important questions about pharmacological smoking cessation aides, namely, how do these therapies affect these two distinct actions of nicotine?…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this may be the complex motivational effects of nicotine; smoking (Rose et al, 2003) and nicotine selfadministration (Donny et al, 2003) are behaviors that depend on more than simple primary reinforcement by nicotine. For example, in rodent self-administration we have found that nicotine has a potent 'reinforcement enhancing' effect in which drug administration increases the rate of responding for reinforcing sensory stimuli Donny et al, 2003). This enhancing effect is thought to derive from a change in the reinforcing properties of the stimulus (Palmatier et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dissertation will review the utility of the drug selfadministration paradigm in extending our understanding of nicotine reinforcement. Recent data demonstrating an interaction between nicotine and nonpharmacological stimuli will be presented to illustrate the novel hypothesis that nicotine reinforcement derives from at least two sources: 1) the primary reinforcing properties of nicotine, an action that requires response-dependent drug administration, and 2) the more prominent ability of nicotine to enhance operant responding for reinforcing non-nicotine stimuli, an action that does not require a contingent relationship between drug administration and reinforced operant behavior (see Table 1; Donny et al 2003).…”
Section: General Introductionmentioning
confidence: 99%